Polygyny, Fertility, and Savings - Tertilt, Michèle (Journal of Political Economy, 2005)
Sub‐Saharan Africa has a high incidence of polygyny. It is also the poorest region of the world. In this paper I ask whether banning polygyny could play any role for development. Using a quantitative model of polygyny, I find that enforcing monogamy lowers fertility, shrinks the spousal age gap, and reverses the direction of marriage payments. Polygyny leads to high bride‐prices to “ration” women, which makes buying wives and selling daughters a good investment, thus crowding out investment in physical assets. For reasonable parameter values, I find that banning polygyny decreases fertility by 40 percent, increases savings by 70 percent, and increases output per capita by 170 percent.